The Map of Transmilenio : Representation, System, and City - Valderrama Pineda , Andrés Felipe (STS Encounters, 2011)
In this paper, I address the following questions: What do experts negotiate when they discuss the contents of a map of a transportation system? Is it a negotiation of a purely representational tool or is the negotiation also about what the transportation system is and how it should evolve? What implications does this have for the development of the city of Bogotá? Departing from Peirce’s triad of index, symbol and icon, I trace the discussions surrounding the evolution of the map of the urban transportation system Transmilenio in the city of Bogotá. I find that the experts involved were not only negotiating the representational contents (symbol and interpretant), but also the system itself (object and index). I also suggest how a map as an icon can have consequences for the city. Therefore, I propose to analyse the map as a screening device to avoid the limitations of a purely representational analysis.